Healthcare Assistants: distributional losses as a consequence of NHS modernisation?. (November 2015) - Clark, Ian; Thompson, Amanda
Abstract : This paper examines the labour process of Healthcare Assistants (HCAs) at a National Health Service (NHS) hospital trust (TUH) in the context of the NHS modernisation agenda. It determines whether application of the modernisation agenda is formalised at TUH and considers how HCAs are affected. The paper is based upon 60 interviews with HCAs, structured questionnaires completed by all interview respondents, observation of HCAs and interviews with non‐clinical managers. The findings show that elements of the modernisation agenda are informally implemented at TUH to the detriment of HCAs. HCAs experience distributional losses in the form of intensification as nurses deflect duties to HCAs and insulate themselves from adverse effects. HCAs resist, using selective absence when pressures mount. They ameliorate losses by re‐internalising their work as a job with caring elements not a genuine caring role. They rationalise their altered behaviour towards patients by blaming the regime's treatment of them as a subordinated group.